The Utilization of Chicken Feather Meal Fermented Using Bacillus sp. From Giant Freshwater Prawn (Macrobrachium rosenbergii) For Fish Feed of Barramundi(Lates calcarifer, Bloch) Fingerling - Alghifari, M Faisal; Adelina, Adelina; Aryani, Netti (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACTThis research was conducted on May-July 2017. The purpose of this research was to determine the utilization of fermented chicken feather meal on artificial feed barramundi and to obtain additional levels of the best feather meal in feed formulation barramundi fingerling, digestibility, growth, feed efficiency and protein retention. This study uses a completely randomized design (CRD) of the factors with 5 treatments and 3 replicated. The treatment in this study was the addition of fermented feather meal that is P1 (0%), P2 (5%), P3 (10%), P4 (15%), P5 (20%) in feed. Protein for feed test average was 45%. The results show that the best treatment material is P5 (20%). The use of 20% chicken feather meal fermentation to produce feed digestibility of 29,58%, feed efficiency of 20,86%, 25,47%protein retention and specific growth rate of 2,34%.Keywords: chicken feather meal, Bacillus sp., Fermentation, barramundi(Latescalcarifer, Bloch), artificial feed